Serial selves : identity and representation in autobiographical comics - Køhlert, Frederik Byrn (Rutgers University Press, 2019)
Autobiography is one of the most dynamic and quickly-growing genres in contemporary comics and graphic narratives. In Serial Selves, Frederik Byrn Køhlert examines the genre's potential for representing lives and perspectives that have been socially marginalized or excluded. With a focus on the comics form's ability to produce alternative and challenging autobiographical narratives, thematic chapters investigate the work of artists writing from perspectives of marginality including gender, sexuality, disability, and race, as well as trauma. Interdisciplinary in scope and attuned to theories and methods from both literary and visual studies, the book provides detailed formal analysis to show that the highly personal and hand-drawn aesthetics of comics can help artists push against established narrative and visual conventions, and in the process invent new ways of seeing and being seen. As the first comparative study of how comics artists from a wide range of backgrounds use the form to write and draw themselves into cultural visibility, Serial Selves will be of interest to anyone interested in the current boom in autobiographical comics, as well as issues of representation in comics and visual culture more broadly.